Implementasi Teknik Reportase untuk Penulisan Naskah Video Feature - Iwan Koswara; Rinda Aunillah; Ghathfan Ariiq Muhammad (Comit: Communication, Information and Technology Journal, 2024)
The development of technology continues to grow rapidly, with the presence of social media being one of the evidences of this technological advancement. The diversity of social media today also influences the types of content that can be presented on these platforms, one of which is video. In the video production process, a scriptwriter plays a crucial role. There are various types of videos, one of which is a feature video that covers a factual or real event. Producing a factual feature video can be achieved by applying reporting techniques to the scriptwriting process. Therefore, the role of the scriptwriter is very important, and the application of these reporting techniques is expected to assist in gathering the necessary facts and data to ensure that the resulting feature video is factual and truly reflects events occurring in society. The method used is a descriptive method, explaining based on the author's experience as a scriptwriter in creating feature videos. It is hoped that this writing can provide new insights into how to apply reporting techniques to feature video scriptwriting.